Dzielimy Się DoświadczeniamiPathology and risk factors of acute coronary syndromes in young people - Gorgoń-Komor, Agnieszka; Gąsior, Mariusz; Komor, Klaudiusz; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The issue of the incidence of acute coronary syndromes (ACS) in the population of young people in correlation with risk factors and atherothrombosis pathology, which can lead to myocardial infarction and sometimes to sudden death, is presented. The scientists emphasise the importance of genetic background of this disease in young people, exploring the genes responsible for lipid disorders and seeking genetic markers of this problem. Arteriosclerosis as a disease starts in early childhood, and new examinations show that it starts before birth. This achievement can deliver very important knowledge to practice and encourage physicians in the aggressive modification of risk factors, which is particularly important in this population.